Novel in-growth core system enables functional studies of grassland mycorrhizal mycelial networks - Johnson, D (The New phytologist, 2001)
•  A novel in-growth core system, enabling functional studies of natural communities of arbuscular mycorrhizal (AM) mycelia in soil is described and tested. •  The cores have windows covered with nylon mesh of 35 µm pore size that prevent in-growth of roots but permit penetration of AM hyphae. They were inserted into grassland turf and contained either sterilized sand and a 'bait' seedling of Trifolium repens or nonsterile natural soil without bait plants. The impacts of hyphal severance, achieved by periodic rotation of some of the cores, upon AM colonization of bait plants (experiment 1) and transfer of 33 P from soil to plants outside the cores (experiment 2) were examined. •  Severance of AM hyphae reduced both AM colonization of bait plants and their shoot P concentrations. The shoot 33 P concentrations of plants with mycelial access to 33 PO4 -labelled cores were 10-fold greater than those which had no mycelial access. •  It is concluded that this novel approach enables the functioning of mycorrhizal mycelial networks to be evaluated under conditions closely simulating those occurring in nature